The theory of quantitative economic policy with applications to economic growth, stabilization and planning. - Fox, Karl A.; Thorbecke, Erik; Sengupta, Jatikumar (Amsterdam ; New York : North-Holland Pub. Co. ; American Elsevier, 1973)
Original edition was published in 1966 under title: The theory of quantitative economic policy with applications to economic growth and stabilization.
Includes bibliographical references.
lje 16/10/18
Loans
Keywords: Economic policy